1986
DOI: 10.1136/adc.61.6.612
|View full text |Cite
|
Sign up to set email alerts
|

Care by parents of their children in hospital.

Abstract: A care by parent option was introduced into a general paediatric ward without any additional finance or facilities. Most parents coped successfully and were grateful for the opportunity of caring for their children. All believed that their children benefited from their active involvement. The nurses believed that their role was enhanced and their job satisfaction increased. This system offers advantages and could become more generally used in paediatric wards in Britain. 1981;10:4-7. 13 Fore CU, Holmes SS. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Policymakers and researchers have raised concerns about the availability of work opportunities for those with the educational levels and job skills of parents currently receiving welfare. 28 Nonetheless, under the new law the majority of welfare recipients will be required to find work within 2 years. Recipients may not receive income support for more than 5 years during their lifetime, and states are granted authority to impose shorter time limits.9…”
Section: S Jody Heymann MD Phd and Alison Earle Phdmentioning
confidence: 99%
“…Policymakers and researchers have raised concerns about the availability of work opportunities for those with the educational levels and job skills of parents currently receiving welfare. 28 Nonetheless, under the new law the majority of welfare recipients will be required to find work within 2 years. Recipients may not receive income support for more than 5 years during their lifetime, and states are granted authority to impose shorter time limits.9…”
Section: S Jody Heymann MD Phd and Alison Earle Phdmentioning
confidence: 99%
“…There is a growing awareness of the need to treat whole families when paediatric problems present (Sainsbury et al, 1986). The development of this thinking can be traced back to the 1950s when theories of attachment were applied to parent-child separations following admissions to hospital (Bowlby, 1971;Robertson, 1958).…”
Section: Introductionmentioning
confidence: 99%
“…The development of research into the psychological sequelae of childhood chronic illness also served to highlight the importance of involving families in treatment (Bradford, 1990;Wallander et al, 1989). Optimal care encourages parents to stay with their ill child in hospital and to take an active role in preparing and helping their child cope with the experience (Sainsbury et al, 1986). Paediatricians, in turn, have had to develop an increasingly sophisticated understanding of the emotional needs of children and their families (Munson, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In the United Kingdom in 1962, 52% of children were accompanied in hospitals, and this reached 60% in 1985 when facilities for mothers had been greatly improved. 3 The age of the hospitalized child is an important factor in the mother's decision to stay in the hospital. Children most likely to be accompanied are between 1 and 2 years old.…”
mentioning
confidence: 99%
“…2 The medical and nursing staff learn to appreciate and understand the mother's problems, and their job satisfaction is increased. 3 The factors that may interfere with a mother's decision to stay in the hospital with the child are the age of the sick child, number of other sibs at home, and the attitude of the medical staff. 4 Others have concluded that child care or job responsibilities, age or sex of the child, and social class are not related to visiting.…”
mentioning
confidence: 99%